A Graphical Tool Support to Process and Simulate ECATNets Models based on Meta-Modelling and Graph Grammars - Kerkouche, Elhillali; Chaou, Allaoua (INFOCOMP Journal of Computer Science, 2009)
ECATNets are an algebraic Petri net category based on a safe combination of algebraic abstract types and high level Petri Nets. ECATNets’ semantic are defined in terms of rewriting logic allowing us to built models by formal reasoning. Furthermore, the rewriting logic language Maude gives to ECATNEts dynamic aspects which are not measurable without simulation. The building of a modelling tool for the design and analysis from scratch (for ECATNets for example) is generally prohibitive task. MetaModelling approach is useful to deal with this problem, as it allows (possibly is done graphically) the modelling of the formalisms themselves. Since meta-model and model are graphs, further manipulations âˆ’simulation, transformation and code generation for an existing solverâˆ’ of the models can be described graphically and formally as graph grammar. In this paper, we propose an approach based on the combined use of Meta-modelling and Graph Grammars to automatically generate a visual modelling tool for ECATNets for analysis and simulation purposes. In our approach, the UML Class diagram formalism is used to define a meta-model of ECATNets. The meta-modelling tool ATOM3 is used to generate a visual modelling tool according to the proposed ECATNets meta-model. We have also proposed a graph grammar to generate Maude description of the graphically specified ECATNets models. Then the rewriting logic language Maude is used to perform the simulation of the resulted Maude specification. Our approach is illustrated through an example.